Carbon-coated silicon-oxygen negative electrode material and preparation method thereof
By forming a three-dimensional collaborative covering strategy of three-dimensional covering structure and two-dimensional electron conduction channel on the surface of the silicon oxygen negative electrode material, the problem of unbalanced current density and poor expansion during the charge and discharge process of silicon oxygen negative electrode material is solved, and higher cyclic stability and lower expansion rate are achieved.
Patent Information
- Application Number
- CN202510069190.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-16
AI Technical Summary
During the charging and discharging process, the current density of the negative electrode surface is unbalanced due to electronic conductivity problems, resulting in the expansion of the anisotropy of the material, resulting in poor stability.
Through silicon oxygen surface modification treatment, a stable three-dimensional coating structure composed of small amino molecules organic matter and carbon nanotubes of the inner layer is formed, and a two-dimensional conductive electron fast channel is combined with the outer layer of the potassium chloride/gelatin system, and finally a three-dimensional coordinated coating strategy of interspersed conductive network and two-dimensional conductive electron channel is formed.
The dual requirements of two-dimensional coated electronic paths and three-dimensional conductivity of the material are realized, which improves the electronic transmission efficiency and structural stability of the material, improves the charge and discharge cycle stability and reduces the expansion rate.
Smart Images

Figure CN119864400A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemistry, and in particular to a method for preparing a silicon monoxide negative electrode material. Background Art
[0002] Compared with elemental silicon particles, silicon oxide (SiOx) undergoes less volume expansion during the lithium embedding process. Therefore, its cycle stability is significantly improved compared to pure silicon negative electrodes. Japan's Shin-Etsu Chemical, South Korea's Dazhou, China's Shanshan Co., Ltd. and BYD Battery can all mass-produce silicon-oxygen negative electrodes. However, silicon oxide negative electrodes will produce inactive substances such as Li2O during the charging and discharging process, resulting in a low first efficiency of SiOx materials (about 70%). The root cause is that the SEI layer that has been formed repeatedly breaks and repeatedly contacts the electrolyte to form a new interface layer, consuming active lithium. Therefore, in order to promote the industrialization of silicon-oxygen negative electrode materials, it is necessary to solve the problems of cycle stability and low first efficiency from the perspective of the uniformity and stability of carbon coating on the surface of the material, and strive to obtain a uniform and dense carbon coating.
[0003] Chinese patent CN113889596A discloses a method for preparing a nitrogen-doped hard carbon-coated artificial graphite composite material. After oxidizing artificial graphite and oxidizing a hard carbon precursor of an amino resin or an amino epoxy resin, the two are allowed to undergo a chemical reaction at 100 to 300°C to achieve the coating of graphite by hard carbon. The macromolecular characteristics of the resin in this coating strategy easily form a hard carbon layer of agglomeration on the graphite surface. It is precisely because of the large resin molecules that the steric hindrance effect is significantly unfavorable for the formation of a thin and uniform coating structure. Moreover, the high reaction temperature will cause the coated organic matter to decompose prematurely, affecting the coating structure. In addition, the conductivity type inside the coated carbon structure layer is single, which is not conducive to electron transmission and ion migration. It is urgent to develop a low-temperature reaction to form a precursor, and further a high-temperature carbonization coating reaction process to form a multi-dimensional carbon coating network to better improve the electronic transmission efficiency of the material.
[0004] Chinese patent CN112635734A discloses a preparation method and application of carbon nanotube-loaded carbon-coated silicon oxide material. The carbon nanotube-loaded carbon-coated silicon oxide material uses carboxylated carbon nanotubes as a skeleton, uses an electrostatic adsorption method to adsorb amino-modified nano-silicon dioxide to its surface, and uses a carbon source liquid phase coating. After the solution penetrates the silicon dioxide, it undergoes a pre-oxidation and carbonization stage, and then undergoes a high-temperature reduction treatment in a hydrogen and argon mixed gas for a certain period of time, and then most of the silicon dioxide is etched away, and finally washed, dried, and ball-milled to obtain a carbon nanotube-loaded carbon-coated silicon oxide powder with a reinforced concrete structure. This method uses carbon tubes as a skeleton to electrostatically adsorb nano-silicon dioxide on the surface, solving the problem that carbon nanotubes are easy to agglomerate and difficult to disperse. Among them, the electrostatic adsorption force is weak, which is still useful for nano-scale silicon dioxide, but this force is applicable to narrow particle sizes, and the further coating of the carbon layer easily destroys the aforementioned force, resulting in the destruction of the adsorbed particle structure, forming a coating configuration that is difficult to maintain. Summary of the invention
[0005] Aiming at the technical problem that the silicon-oxygen negative electrode material prepared by the prior art has an uneven current density on the negative electrode surface due to the problem of electronic conductivity, which further leads to anisotropic expansion of the material and poor stability. The present invention proposes a carbon-coated silicon-oxygen negative electrode material and a preparation method thereof. After the silicon-oxygen surface is modified, a stable three-dimensional coating structure consisting of an inner layer of amino small molecule organic matter and carbon nanotubes is formed by covalent bonding, and then combined with the two-dimensional fast electron channel of the outer layer of the potassium chloride / gelatin system, a three-dimensional synergistic coating strategy of interlaced conductive networks and two-dimensional conductive electron channels is finally formed, so as to prepare a negative electrode material that meets the dual requirements of two-dimensional coated electronic pathways and three-dimensional conductivity.
[0006] To achieve the above object, the technical solution of the present invention is implemented as follows:
[0007] A method for preparing a carbon-coated silicon-oxygen negative electrode material, comprising the following steps:
[0008] (1) adding a silane coupling agent and succinic anhydride to N,N-dimethylformamide (DMF) for dispersion, adding a DMF suspension of silicon dioxide and water, hydrolyzing the silane coupling agent, heating and stirring, chemically reacting the hydrolyzed coupling agent, anhydride and silicon dioxide, centrifuging and washing with ethanol to obtain a surface carboxyl-modified silicon dioxide material, i.e., precursor A;
[0009] (2) dissolving gelatin and potassium chloride in deionized water, and adding precursor A to obtain dispersion B; dispersing a water-soluble crosslinking agent containing an amino group and amino carbon nanotubes or amino graphene in water to obtain dispersion C;
[0010] (3) Dispersion C is added to dispersion B to obtain solution D, which is heated and stirred. At this time, the cross-linking agent, the amino groups on the carbon tubes and the carboxyl groups on the surface of the silicon oxide are bonded to form a coating. Gelatin and potassium chloride are present in the aqueous solution. After spray drying, potassium chloride and gelatin as solutes are instantaneously dried in situ on the coating structure with the bonded amino compound to form a two-dimensional coating structure. After high-temperature carbonization, a three-dimensional coating layer is formed. After further washing away the potassium chloride in the outer two-dimensional coating structure, a silicon oxide negative electrode material with a firm inner coating and a porous three-dimensional carbon coating on the outer surface is obtained.
[0011] In the above step (1), the molar ratio of the silane coupling agent to succinic anhydride is 1:(1-1.2); the mass ratio of succinic anhydride, water and silicon dioxide is 1:2:(0.7-1.3).
[0012] Furthermore, in step (1), the silane coupling agent is any one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane and ethylaminopropyltrimethoxysilane.
[0013] The heating and stirring temperature in the above step (1) is 50-80°C and the time is 1-5h.
[0014] The mass ratio of gelatin, potassium chloride and precursor A in the dispersion B of the above step (2) is 1:10:(1-1.5).
[0015] In the above step (3), the mass ratio of the water-soluble crosslinking agent containing amino groups, the precursor A, the amino carbon nanotubes or the amino graphene to the solution D is 1:(10-15):(0.005-0.01).
[0016] Furthermore, the amino group-containing water-soluble crosslinking agent is at least one of ethylene glycol amine, triethanolamine and hexamethoxymethyl melamine.
[0017] In the above step (3), the temperature of heating and stirring is 50-90°C and the time is 10-24h; the temperature of high temperature carbonization is 700-800°C and the time is 1-5h.
[0018] In the above step (3), the spray drying can be carried out by means of dual-fluid spray drying, centrifugal atomizing disk spray drying or pressure spray drying; the high-temperature carbonization is carried out in a pure inert gas such as argon and nitrogen.
[0019] The carbon-coated silicon-oxygen negative electrode material is prepared by the above-mentioned preparation method.
[0020] Application of the above-mentioned carbon-coated silicon-oxygen negative electrode material in lithium-ion batteries.
[0021] The beneficial effects produced by the present invention are:
[0022] (1) The present invention utilizes the principle of chemical bonding between amino carbon tubes or amino graphene and small molecule amino crosslinkers and carboxylated silicon-oxygen materials, and in situ chemically bonds the crosslinker and carbon tube / graphene on the silicon-oxygen surface by heating, thereby forming a precursor with a firm coating on the surface. In addition, a high concentration of potassium chloride and gelatin are instantaneously deposited on the surface of the precursor by means of a spray drying method, and after high-temperature reaction and cleaning, a three-dimensional coating structure with carbon tubes interspersed inside and a porous channel coating layer on the outside is formed. First, the porous characteristics of the outer layer of this structure are conducive to electrolyte infiltration, increase the amount of electrode liquid retention, easily shorten the carrier transmission distance, improve the surface charge transfer efficiency, and reduce the expansion caused by uneven ion reactions; second, this outer layer structure buffers the internal expansion stress, offsets the expansion space, and further reduces the macroscopic expansion effect. In addition, the inner stable coating layer blocks the electrolyte from further side reactions, improves the structural stability of the negative electrode material and the uniformity of the surface current density, thereby improving the charge and discharge cycle stability and reducing the expansion of the silicon-carbon negative electrode material.
[0023] (2) The carbon-coated silicon-oxygen negative electrode material prepared by the present invention has a stable capacity of 1550 mAh / g at a current density of 1000 mA / g, and after 100 cycles, the capacity retention rate of the battery is 96%, and the expansion rate of the electrode can be as low as 112%. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 This is an electron microscope image of the structure of the carbon-coated silicon oxygen negative electrode material prepared in Example 1 of the present invention.
[0026] Figure 2 This is an electron microscope image of the structure of the carbon-coated silicon-oxygen negative electrode material prepared in Comparative Example 3 of the present invention.
[0027] Figure 3 This is a half-cell discharge capacity cycle performance diagram of materials in Example 1 of the present invention and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] The preparation method of the carbon-coated silicon-oxygen negative electrode material of this embodiment comprises the following steps:
[0031] (1) 5 mmol of γ-aminopropyltriethoxysilane and 5 mmol of succinic anhydride were uniformly dispersed in 50 mL of DMF, stirred at 70° C. for 1 h, and then 5 g of silicon dioxide (mass fraction 10%) was added to the DMF dispersion, and then 1 g of water was added. The mixture was heated and stirred at 50° C. for 5 h and then centrifuged. After washing with ethanol three times, the mixture was dried to obtain a surface carboxyl-modified silicon dioxide material, i.e., precursor A.
[0032] (2) Dissolve 5 g of gelatin and 50 g of potassium chloride in 500 mL of deionized water, heat at 50°C and stir, then add 5 g of surface carboxyl modified silicon oxide material to the above solution, and stir continuously at 50°C to obtain a dispersion. Take 0.5 g of ethylene glycol amine and 0.005 g of amino carbon nanotubes in ultrasonically dispersed water, then add them to the above dispersion and stir, heat at 50°C and stir for 24 hours, then spray dry to obtain a precursor.
[0033] (3) The precursor was transferred to a sintering furnace and sintered at 700°C for 5 h under Ar atmosphere protection. After three water washes to remove potassium chloride, a carbon-coated silicon-oxygen negative electrode material was obtained.
[0034] The microstructure of the samples prepared in this example was measured using a Hitachi S-3400N scanning electron microscope. Figure 1 The surface of the material shows an irregular multi-open pore structure, with light and dark staggered edges and corners, small rough particles, and occasional carbon tubes, indicating that after washing and removing the soluble potassium chloride, pores are formed to form a porous structure surface. The light and dark staggered edges may be carbon layers and carbon particles with better conductivity.
[0035] Example 2
[0036] The preparation method of the carbon-coated silicon-oxygen negative electrode material of this embodiment comprises the following steps:
[0037] (1) 10 mmol of γ-aminopropyltriethoxysilane and 12 mmol of succinic anhydride were uniformly dispersed in 100 mL of DMF, stirred at 50° C. for 5 h, and then 8.4 g of silicon dioxide (mass fraction 10%) dispersed in DMF was added thereto. After adding 2.4 g of water, the mixture was heated and stirred at 50° C. for 5 h and then centrifuged. After washing with ethanol three times, the mixture was dried to obtain a surface carboxyl-modified silicon dioxide material, i.e., precursor A.
[0038] (2) Dissolve 7 g of gelatin and 70 g of potassium chloride in 700 mL of deionized water, heat at 50°C and stir, then add 10.5 g of surface carboxyl modified silicon oxide material to the above solution, and stir continuously at 50°C to obtain a dispersion. Take 0.7 g of ethylene glycol amine and 0.0035 g of amino carbon nanotubes in ultrasonically dispersed water, then add them to the above dispersion and stir, heat at 90°C and stir for 10 h, then spray dry to obtain a precursor.
[0039] (3) The precursor was transferred to a sintering furnace and sintered at 800°C for 1 hour under Ar atmosphere protection. After three water washes to remove potassium chloride, a carbon-coated silicon-oxygen negative electrode material was obtained.
[0040] Example 3
[0041] The preparation method of the carbon-coated silicon-oxygen negative electrode material of this embodiment comprises the following steps:
[0042] (1) 7 mmol of γ-aminopropyltrimethoxysilane and 7 mmol of succinic anhydride were uniformly dispersed in 70 mL of DMF, stirred at 60° C. for 4 h, and a DMF dispersion containing 6 g of silicon dioxide (mass fraction of 10%) was added thereto. After adding 1.4 g of water, the mixture was heated and stirred at 60° C. for 3 h and then centrifuged. After washing with ethanol three times, the mixture was dried to obtain a surface carboxyl-modified silicon dioxide material, i.e., precursor A.
[0043] (2) 6 g of gelatin and 60 g of potassium chloride were dissolved in 600 mL of deionized water, heated at 50°C and stirred, and 6 g of surface carboxyl modified silicon oxide material was added to the above solution, and stirred continuously at 50°C to obtain a dispersion. 0.6 g of ethylene glycol amine and 0.0045 g of amino carbon nanotubes were ultrasonically dispersed in water, and then added to the above dispersion and stirred, heated at 80°C and stirred for 12 h, and then spray dried to obtain a precursor.
[0044] (3) The precursor was transferred to a sintering furnace and sintered at 750°C for 2 h under Ar atmosphere protection. After three water washes to remove potassium chloride, a carbon-coated silicon-oxygen negative electrode material was obtained.
[0045] Example 4
[0046] The preparation method of the carbon-coated silicon-oxygen negative electrode material of this embodiment comprises the following steps:
[0047] (1) 8 mmol of γ-aminopropyltrimethoxysilane and 8 mmol of succinic anhydride were uniformly dispersed in 80 mL of DMF, stirred at 60° C. for 2 h, and a DMF dispersion containing 9 g of silicon dioxide (mass fraction of 10%) was added thereto. After adding 1.6 g of water, the mixture was heated and stirred at 60° C. for 3 h and then centrifuged. After washing with ethanol three times, the mixture was dried to obtain a surface carboxyl-modified silicon dioxide material, i.e., precursor A;
[0048] (2) 9 g of gelatin and 90 g of potassium chloride were dissolved in 900 mL of deionized water, heated at 50°C and stirred, and then 11.7 g of surface carboxyl modified silicon oxide material was added to the above solution, and continuously stirred at 50°C to obtain a dispersion. 0.9 g of hexamethoxymethyl melamine and 0.0075 g of amino carbon nanotubes were ultrasonically dispersed in water, then added to the above dispersion and stirred, heated at 70°C and stirred for 18 h, and then spray dried to obtain a precursor.
[0049] (3) The precursor was transferred to a sintering furnace and sintered at 750°C for 2 h under N2 atmosphere protection. After three water washes to remove potassium chloride, a carbon-coated silicon-oxygen negative electrode material was obtained.
[0050] Example 5
[0051] The preparation method of the carbon-coated silicon-oxygen negative electrode material of this embodiment comprises the following steps:
[0052] (1) 6 mmol of aminoethylaminopropyltrimethoxysilane and 6 mmol of succinic anhydride were uniformly dispersed in 60 mL of DMF, stirred at 70° C. for 2 h, and a DMF dispersion containing 7 g of silicon dioxide (mass fraction of 10%) was added thereto. After adding 1.2 g of water, the mixture was heated and stirred at 70° C. for 2 h and then centrifuged. The mixture was washed with ethanol three times and then dried to obtain a surface carboxyl-modified silicon dioxide material, i.e., precursor A;
[0053] (2) Dissolve 7 g of gelatin and 70 g of potassium chloride in 700 mL of deionized water, heat at 50°C and stir, then add 7 g of surface carboxyl modified silicon oxide material to the above solution, and stir continuously at 50°C to obtain a dispersion. Take 0.7 g of triethanolamine and 0.0045 g of amino carbon nanotubes in ultrasonically dispersed water, then add them to the above dispersion and stir, heat at 50°C and stir for 12 h, then spray dry to obtain a precursor.
[0054] (3) The precursor was transferred to a sintering furnace and sintered at 720°C for 2 h under N2 atmosphere protection. After three water washes to remove potassium chloride, a carbon-coated silicon-oxygen negative electrode material was obtained.
[0055] Example 6
[0056] The preparation method of the carbon-coated silicon-oxygen negative electrode material of this embodiment comprises the following steps:
[0057] (1) 7 mmol of aminoethylaminopropyltrimethoxysilane and 7.7 mmol of succinic anhydride were uniformly dispersed in 70 mL of DMF, stirred at 80° C. for 4 h, and a DMF dispersion containing 6 g of silicon dioxide (mass fraction of 10%) was added thereto. After adding 1.54 g of water, the mixture was heated and stirred at 80° C. for 3 h and then centrifuged. After washing with ethanol three times, the mixture was dried to obtain a surface carboxyl-modified silicon dioxide material, i.e., precursor A.
[0058] (2) 6 g of gelatin and 60 g of potassium chloride were dissolved in 600 mL of deionized water, heated at 50°C and stirred, and 6 g of surface carboxyl modified silicon oxide material was added to the above solution, and stirred continuously at 50°C to obtain a dispersion. 0.6 g of hexamethoxymethyl melamine and 0.0055 g of amino carbon nanotubes were ultrasonically dispersed in water, and then added to the above dispersion and stirred, heated at 70°C and stirred for 16 h, and then spray dried to obtain a precursor.
[0059] (3) The precursor was transferred to a sintering furnace and sintered at 700°C for 2 h under Ar atmosphere protection. After three water washes to remove potassium chloride, a carbon-coated silicon-oxygen negative electrode material was obtained.
[0060] Example 7
[0061] The preparation method of the carbon-coated silicon-oxygen negative electrode material of this embodiment comprises the following steps:
[0062] (1) 5 mmol of aminoethylaminopropyltrimethoxysilane and 5 mmol of succinic anhydride were uniformly dispersed in 50 mL of DMF, stirred at 80° C. for 1 h, and a DMF dispersion containing 6 g of silicon dioxide (mass fraction of 10%) was added thereto. After adding 1 g of water, the mixture was heated and stirred at 80° C. for 3 h and then centrifuged. After washing with ethanol three times, the mixture was dried to obtain a surface carboxyl-modified silicon dioxide material, i.e., precursor A.
[0063] (2) Dissolve 6 g of gelatin and 60 g of potassium chloride in 600 mL of deionized water, heat at 50°C and stir, then add 6 g of surface carboxyl modified silicon oxide material to the above solution, and stir continuously at 50°C to obtain a dispersion. Take 0.6 g of ethylene glycol amine and 0.005 g of amino carbon nanotubes in ultrasonically dispersed water, then add them to the above dispersion and stir, heat at 70°C and stir for 12 h, then spray dry to obtain a precursor.
[0064] (3) The precursor was transferred to a sintering furnace and sintered at 750°C for 2 h under Ar atmosphere protection. After three water washes to remove potassium chloride, a carbon-coated silicon-oxygen negative electrode material was obtained.
[0065] Comparative Example 1
[0066] The preparation method of the carbon-coated silicon-oxygen negative electrode material in this comparative example is different from that in Example 1 in that the silicon oxide is not carboxylated and modified, and the steps are as follows:
[0067] (1) Dissolve 5 g of gelatin and 50 g of potassium chloride in 500 mL of deionized water, heat at 50°C and stir, then add 5 g of silicon oxide raw material to the above solution, and continue stirring at 50°C to obtain a dispersion. Take 0.5 g of ethylene glycol amine and 0.005 g of amino carbon nanotubes in ultrasonically dispersed water, then add them to the above dispersion and stir, heat at 50°C and stir for 24 hours, then spray dry to obtain a precursor.
[0068] (2) The precursor was transferred to a sintering furnace and sintered at 700°C for 5 h under Ar atmosphere protection. After three water washes to remove potassium chloride, a carbon-coated silicon-oxygen negative electrode material was obtained.
[0069] Comparative Example 2
[0070] The method for preparing the carbon-coated silicon-oxygen negative electrode material in this comparative example is different from that in Example 1 in that no heating operation is performed in step (2), and the steps are as follows:
[0071] (1) 5 mmol of γ-aminopropyltriethoxysilane and 5 mmol of succinic anhydride were uniformly dispersed in 50 mL of DMF, stirred at 70° C. for 1 h, and then 5 g of silicon dioxide (mass fraction 10%) was added to the DMF dispersion, and then 1 g of water was added. The mixture was heated and stirred at 50° C. for 5 h and then centrifuged. After washing with ethanol three times, the mixture was dried to obtain a surface carboxyl-modified silicon dioxide material, i.e., precursor A.
[0072] (2) Dissolve 5 g of gelatin and 50 g of potassium chloride in 500 mL of deionized water, stir, take 5 g of surface carboxyl modified silicon oxide material and add it to the above solution, and continue stirring to obtain a dispersion. Take 0.5 g of ethylene glycol amine and 0.005 g of amino carbon nanotubes in ultrasonic dispersion water, then add them to the above dispersion and stir, stir for 24 hours, then spray dry to obtain a precursor.
[0073] (3) The precursor was transferred to a sintering furnace and sintered at 700°C for 5 h under Ar atmosphere protection. After three water washes to remove potassium chloride, a carbon-coated silicon-oxygen negative electrode material was obtained.
[0074] Comparative Example 3
[0075] The preparation method of the carbon-coated silicon-oxygen negative electrode material in this comparative example is different from that in Example 1 in that gelatin and potassium chloride are not added in step (2), and the steps are as follows:
[0076] (1) 5 mmol of γ-aminopropyltriethoxysilane and 5 mmol of succinic anhydride were uniformly dispersed in 50 mL of DMF, stirred at 70° C. for 1 h, and then 5 g of silicon dioxide (mass fraction 10%) was added to the DMF dispersion, and then 1 g of water was added. The mixture was heated and stirred at 50° C. for 5 h and then centrifuged. After washing with ethanol three times, the mixture was dried to obtain a surface carboxyl-modified silicon dioxide material, i.e., precursor A.
[0077] (2) 5 g of surface carboxyl modified silicon dioxide material was added to deionized water and stirred continuously at 50° C. to obtain a dispersion. 0.5 g of ethylene glycol amine and 0.005 g of amino carbon nanotubes were ultrasonically dispersed in water, then added to the above dispersion and stirred, heated at 50° C. and stirred for 24 h, and then spray dried to obtain a precursor.
[0078] (3) The precursor was transferred to a sintering furnace and sintered at 700°C for 5 h under Ar atmosphere protection to obtain carbon-coated silicon oxide powder. After three water washes, the carbon-coated silicon oxide negative electrode material was obtained. Figure 2 The SEM image of the carbon-coated silicon-oxygen negative electrode material prepared in this comparative example clearly shows the composite structure of the amorphous carbon layer and the carbon tubes, indicating that the surface is coated with uniform amorphous carbon and a three-dimensional carbon layer in which the carbon tubes cross and penetrate.
[0079] Application Examples
[0080] The negative electrode materials prepared in the examples of the present invention and the comparative examples were applied to lithium-ion batteries. The battery assembly process and electrochemical performance test results are as follows:
[0081] Button cell: The silicon-oxygen negative electrode material prepared by the present invention is slurried with a conductive agent and a binder in a mass ratio of 8:1:1, uniformly coated on a copper foil and dried to obtain a pole piece, wherein the binder is polyacrylic acid (PAA). A LiPF6 electrolyte with a concentration of 1.0 mol / L is used, wherein the volume ratio of the solvent components ethylene carbonate (EC): diethyl carbonate (DEC): dimethyl carbonate (DMC) is 1:1:1, and 10% of fluoroethylene carbonate (FEC) is added. A microporous polypropylene diaphragm is selected, and a lithium sheet is used as a counter electrode to assemble a CR2025 button half-cell. Comparative Example 1-2 assembles the battery according to the above method, and uses a battery testing system with model LANHE CT2001A produced by Wuhan Landian Electronics Co., Ltd. to test the battery performance.
[0082] The first cycle test uses a current density of 100mA / g and a voltage range of 0.005 to 2.0V. The constant current cycle performance test is carried out at 25°C with a current density of 1000mA / g and a voltage range of 0.005 to 2V. Figure 3 The cycle retention rate (96%) of Example 1 after 100 cycles is significantly better than that of Comparative Example 1 (6%) and Comparative Example 2 (4%). This is because a uniform coating layer is formed on the surface of the silicon oxide particles, which improves the conductivity of the material, accelerates carrier transport, and improves the efficiency of material charging and discharging.
[0083] Full battery pole piece expansion test: The silicon oxygen negative electrode material prepared by the present invention is slurried with a conductive agent and a binder in a mass ratio of 96:1:3, uniformly coated on a copper foil and dried to obtain a negative electrode piece, wherein the binder is polyacrylic acid (PAA). A LiPF6 electrolyte with a concentration of 1.0 mol / L is used, wherein the volume ratio of the solvent components ethylene carbonate (EC): diethyl carbonate (DEC): dimethyl carbonate (DMC) is 1:1:1, and 10% fluoroethylene carbonate (FEC) is added. NCM811 is selected as the positive electrode, and a microporous polypropylene diaphragm is selected. The room temperature cycle current is 0.5C, the rated capacity is 3.7Ah, the voltage range is 2.8-4.2V, the discharge depth is 100% DOD, and the thickness of the silicon negative electrode piece is measured with a micrometer after the cycle (100 laps). The measurement results are shown in Table 1.
[0084] Table 1
[0085]
[0086] Among them, the initial thickness is the designed thickness of the pole piece, the FCC thickness is the thickness of the silicon negative pole piece after the cycle is completed, and the expansion rate = (FCC thickness / initial thickness-1)×100%. It can be seen from the table that the FCC thickness of the pole piece of Example 1 is 205.64μm, and the expansion rate is 112%, and the FCC thickness of Comparative Example 1 is 222.36μm, and the expansion rate is 129.24%. The cycle expansion rate of the pole piece of the embodiment is reduced by 17.24%.
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon-coated silicon-oxygen negative electrode material, characterized in that: Here are the steps: (1) After dispersing the silane coupling agent and succinic anhydride in N,N-dimethylformamide, a DMF suspension of silicon dioxide and water are added, and the precursor A is obtained after heating, stirring, centrifugation and washing; (2) dissolving gelatin and potassium chloride in deionized water, and adding precursor A to obtain dispersion B; dispersing a water-soluble crosslinking agent containing an amino group and amino carbon nanotubes or amino graphene in water to obtain dispersion C; (3) Dispersion C is added to dispersion B to obtain solution D, and after heating and stirring, spray drying, high-temperature carbonization and washing, a carbon-coated silicon oxygen negative electrode material is obtained.
2. The method for preparing the carbon-coated silicon-oxygen negative electrode material according to claim 1, characterized in that: In the step (1), the molar ratio of the silane coupling agent to succinic anhydride is 1:(1-1.2); the mass ratio of succinic anhydride, water and silicon dioxide is 1:2:(0.7-1.3).
3. The method for preparing the carbon-coated silicon-oxygen negative electrode material according to claim 2, characterized in that: The silane coupling agent in step (1) is any one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane and ethylaminopropyltrimethoxysilane.
4. The method for preparing the carbon-coated silicon-oxygen negative electrode material according to claim 3, characterized in that: The heating and stirring in step (1) is performed at a temperature of 50-80° C. and for a time of 1-5 h.
5. The method for preparing the carbon-coated silicon-oxygen negative electrode material according to claim 4, characterized in that: The mass ratio of gelatin, potassium chloride and precursor A in the dispersion B of step (2) is 1:10:(1-1.5).
6. The method for preparing the carbon-coated silicon-oxygen negative electrode material according to claim 5, characterized in that: In the step (3), the mass ratio of the water-soluble crosslinking agent containing amino groups, the precursor A, and the amino carbon nanotubes or amino graphene in the solution D is 1:(10-15):(0.005-0.01).
7. The method for preparing the carbon-coated silicon-oxygen negative electrode material according to claim 6, characterized in that: The water-soluble crosslinking agent containing amino groups is at least one of ethylene glycol amine, triethanolamine and hexamethoxymethyl melamine.
8. The method for preparing the carbon-coated silicon-oxygen negative electrode material according to claim 7, characterized in that: The heating and stirring temperature in step (3) is 50-90°C for 10-24h; the high temperature carbonization temperature is 700-800°C for 1-5h.
9. A carbon-coated silicon-oxygen negative electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the carbon-coated silicon-oxygen negative electrode material according to claim 9 in lithium-ion batteries.
Citation Information
Patent Citations
Preparation method of nitrogen-doped hard carbon coated artificial graphite composite material
CN113889596A
Preparation method and application of carbon nanotube-loaded carbon-coated silica material
CN112635734A
Modified silicon monoxide / carbon nanotube composite negative electrode material and preparation method thereof
CN112678807A
TiO2 nanoflower loaded chitosan microsphere sewage treatment material and preparation method thereof
CN112844329A
Negative electrode material, negative electrode sheet, electrochemical device, and electronic device
CN113728471A